DILEMA KEAMANAN ANTARA TIONGKOK DAN AMERIKA SERIKAT DI KAWASAN INDO-PACIFIC - Adipratama, Agung Kurnia (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2024)
China’s tremendous economic growth from 1978 to 2010s has enabled Beijing to expand military growth for Beijing. This has made China to become more prosperous and stronger than ever before. This is also shifting the balance of power in the Indo-Pacific region, especially when the United States is already being the dominant power since the end of Cold War. Throughout different years the United States has had different perceptions on commenting China’s rise. Since 2020 relations between two countries have been intensified when then Chinese Foreign Minister Wang Yi mentioned the resurfacing of “Cold War” mentality. This essay employed examples from case studies and interactions between leaders and social actors. This essay is going to discuss extensively on the rise of China and the reactions from the United States towards that. Furthermore, it is going to explain how a security dilemma between the two countries occurred that stemmed from the two factors aforementioned. This writing discovered that the rise of China that completely shifted the balance of power is through military presence in South China Sea. China has employed military, diplomatic and economic powers to influence the reality on the ground. This is a reality that United States had to willingly accepted and trying to alter course of balance of power have been the norm for Washington. Lastly, this writing concludes that security dilemma occurred for both countries since the two are suspicious to one another.